PRESUPPOSITIONS AND LEVELS OF UNDERSTANDING IN SCIENTIFIC EXEGESIS: Insights from Indonesian Quranic Scholars - Iqbal, Muhammad; Asfahani, Mohammad Ali Rezaei; Tousi, Hamid Reza (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2024)
This study explores the presuppositions underlying scientific exegesis as discussed by Indonesian Quranic scholars. Focusing on horizontal gradations of understanding, it examines their role in shaping the necessity for scientific interpretation. Since the 1960s, Indonesia has witnessed significant growth in scientific exegesis, leading to the emergence of three distinct generations of exegetical thought. These developments are rooted in foundational presuppositions (mabna), which drive the evolution of interpretive approaches. Using a literature review method, the research analyzes documents and applies content analysis to identify key insights. The study concludes that the horizontal gradation of understanding, reflecting the Qur’an’s comprehensiveness and its numerous scientific verses, serves as the foundational presupposition for Indonesian scientific exegetes in employing scientific methodologies for Quranic interpretation. This approach underscores the dynamic interplay between scientific perspectives and Quranic understanding within the Indonesian context. Keywords: Indonesia, presuppositions of exegesis, Kauni  verses, gradation of understanding, scientific exegesis